Strokovna podpora neformalnim oskrbovalcem v domačem okolju - Drnovšek, Rok (Obzornik zdravstvene nege, 2023)
Introduction: The Older adults in their home environment often need support services of informal caregivers whose role is, therefore, becoming increasingly important in providing home care services. The aim of this literature review is to identify possible interventions to improve professional informal care services of the older adults.Methods: A literature review in CINAHL, PubMed and PubMed Central® databases with integrative data analysis was undertaken. Qualitative analysis focused on the literature about interventions regarding nursing activities for the support provided to informal caregivers of older adults in their home environment or the home environment of their caregivers.Results: The final analysis included ten original research articles that satisfied the inclusion criteria. In the analysis, nine code categories describing the needs of informal caregivers and the characteristics of detected supportive interventions for the support of informal caregivers were formulated.Discussion and conclusion: Individualization, flexibility and promoting an active role of informal caregivers were recognized as important features of interventions to support informal caregivers in their home environment. Education and training of those who conduct interventions should also be considered.
Keywords: empowermen; home care; laična oskrba; lay caregiving; nursing; opolnomočenje; oskrba na domu; starejši odrasli; the elderly; zdravstvena nega